Effects of land-use change on vascular epiphyte diversity in Sumatra (Indonesia). (October 2016) - Böhnert, Tim; Wenzel, Arne; Altenhövel, Christian; Beeretz, Lukas; Tjitrosoedirdjo, Sri Sudarmiyati; Meijide, Ana; Rembold, Katja; Kreft, Holger
Abstract: Land-use change is the main driver of biodiversity loss in the tropics worldwide. Lowland rainforest regions in Southeast Asia are experiencing particularly high rates of large-scale conversion of forests and agroforests into monocultural tree plantations including oil palm and rubber with devastating effects on forest-dependent species. Canopy-dwelling organisms such as epiphytes are expected to be particularly susceptible to changes in land use, vegetation structure, and microclimate but the consequences of these changes are only poorly known for this plant group in Southeast Asia. We investigated the diversity of vascular epiphytes in four major land-use systems in Jambi Province (Sumatra, Indonesia). Epiphyte communities were sampled in 120 20 × 20 m plots in Bukit Duabelas National Park (lowland rainforest) and in surrounding jungle rubber agroforests as well as in rubber and oil palm plantations owned by smallholders. At plot level, lowland rainforest, jungle rubber, and oil palm were statistically indistinguishable in terms of richness, diversity, and evenness but had significantly higher values than rubber. Oil palm plantations had the highest epiphyte abundance, but lowest total species number of all systems. Furthermore, oil palm had distinct, fern-dominated epiphyte communities that differed significantly from the other systems. In conclusion, the value of monocultural tree plantations of oil palms and rubber trees for epiphyte conservation is very low. Jungle rubber, an extensively managed yet vanishing system, represents a refuge for epiphytes and could play a vital role in conserving epiphyte diversity, especially of ferns and orchids. Non-orchid angiosperms, however, mainly occurred in forest and are thus most threatened by forest conversion. Highlights: Significant losses of epiphyte diversity in rubber and oil palm plantations – especially at the land-use system scale. Land-use effects were strongly scale dependent. Change in epiphyte diversity associated with differences in stand structural characteristics, microclimate and management. Highest epiphyte diversity in jungle rubber agroforests. Angiosperms others than orchids mainly occur in forest and are most affected by forest conversion.